Faktor-Faktor Kesediaan Untuk Membayar Beras Kemasan Pada Pasar Swalayan - Ismalia Afriani; Ainul Mardliyah; Supriyadi Supriyadi (Politeknik Negeri Lampung., 2019)
The Change of people's shopping preference from traditional markets to shopping centers and modern markets are strongly facilitated by the development of modern markets (small, medium and large retail). This condition contributes the increasingly marketing of labeled packaged rice which offered by the modern market. The purpose of this study is to determine the factors that influence consumers' willingness to pay for packaged rice at supermarkets. The study was conducted for 4 months in June - September in the City of Bandar Lampung, Lampung Province, using the survey method. The research location was chosen purposively, at the Chandra supermarket and Giant Bandar Lampung. The sampling method used in this study is judgment sampling. The method of analysis has done using logistic regression analysis. The results showed that the factors that influence willingness to pay are bidding price, income and comfort factors. The highest value of odds ratio is owned by income factor which means that consumers who have higher income have the opportunity to buy packaged rice at supermarkets